Pengaruh Budaya Patriaki atas Penafsiran Thaifur Ali Wafa: Analisis Ayat Gender dalam Tafsir Firdaus al-Na’im - Anisa, Siti; Rahmat Hidayatullah, Adi (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2024)
This article discusses the influence of patriarchal culture on Tafsir Firdaus Al-Na'im by Thaifur Ali Wafa, who specifically analyzes the interpretation of gender verses. This research shows that the interpretation of Thaifur Ali Wafa still maintains the patriarchal element which states that a man is the leader of the family with greater responsibilities and rights than a woman. The background concludes that Tafsir Firdaus Al-Na'im still contains strong patriarchal elements because it is influenced by socio-cultural norms of Patriarchy using Classical Tafsir reference sources as well as traditional views on gender relations in Islam accompanied by an emphasis on ethics and responsibility. This research aims at how Tafsir Firdaus Al-Na'im answers contemporary issues occurring in the surrounding community. The research method used is a qualitative method or literature with a descriptive approach by collecting data from two types, namely primary data and secondary data.